QUALITY MANAGEMENT ANALYSIS IN ISLAMIC RELIGIOUS EDUCATION TEXTBOOKS UPPER SECONDARY SCHOOL CHARACTER EDUCATION ORIENTED: QUALITY MANAGEMENT ANALYSIS IN ISLAMIC RELIGIOUS EDUCATION TEXTBOOKS UPPER SECONDARY SCHOOL CHARACTER EDUCATION ORIENTED - Mustaqim, Mustaqim; Masyitoh, Masyitoh; Adawiyah, Rabiatul (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study aims to analyze the quality management of Islamic Religious Education (PAI) textbooks for Senior High Schools (SMA) that are oriented towards character education. The focus of the study is directed at how the planning, implementation, supervision, and evaluation of the quality of PAI textbooks are carried out in accordance with the educational quality standards and character values ​​mandated in the national education policy. This study uses a qualitative approach with descriptive analysis methods. Data were collected through document studies of PAI textbooks for Senior High Schools published by the Ministry of Primary and Secondary Education, in-depth interviews with book authors, editors, and PAI teachers, and observations of book use in the school environment. The results of the study indicate that the quality management of Islamic Religious Education textbooks has met the principles of Total Quality Management (TQM). In terms of planning, the textbooks have been compiled in accordance with curriculum standards, but the systematic integration of character values ​​has not been optimal. In terms of implementation, the writing and editing processes have followed academic publishing mechanisms, but there is still an imbalance between the cognitive, affective, and psychomotor dimensions. In terms of supervision, the quality assurance system has not been implemented in an integrated manner between the author's institution, publisher, and book users. Meanwhile, in terms of evaluation, feedback from teachers and students has not been used effectively to improve the quality of content and learning design. This study concludes that improving the quality of Islamic Religious Education textbooks based on character education requires synergy between managerial, pedagogical, and spiritual aspects. The main recommendation is the need for a quality management model for Islamic Religious Education textbooks that emphasizes the integration of character values ​​in every stage of quality management, from planning to evaluation. The findings of this study are expected to serve as a reference for policymakers, textbook authors, and educators in developing quality and character-based Islamic Religious Education textbooks.